Convection-diffusion-reaction of CO2-enriched brine in porous media: A pore-scale study. (April 2019) - Dashtian, Hassan; Bakhshian, Sahar; Hajirezaie, Sassan; Nicot, Jean-Philippe; Hosseini, Seyyed Abolfazl
Abstract: CO2 -enriched brine interaction with reservoir minerals and the subsequent mineral trapping of CO2 alter the morphology of pore structure. Such changes in the pore space modify the storage capacity of reservoirs and increase the long-term security of CO2 storage. The extent of pore space modification depends on the relative weight of advection, diffusion and reaction mechanisms. We present a general framework for a direct simulation of reactive transport in digitized reservoir rock samples based on a pore-scale modeling in two-dimensional (2D) and three-dimensional (3D) pore-throat networks. We examine the impact of transport properties such as Péclet ( Pe ) and Damköhler ( Da ) numbers, on the petrophysical properties and dissolution of mineral in pore space. We implement marker-based watershed segmentation to extract pore networks of 3D micro-CT (Computerized Tomography) scan images. The extracted network is used to simulate the reactive solute transport and dissolution on real rock samples. This approach enables us to study reaction of CO2 -enriched brine with reservoir rock samples, which is vital in predicting long-term security of CO2 storage. We implement our approach to study CO2 injection in samples from the Cranfield site, Mississippi, U.S.A. We show that for small PeDa numbers, the concentration and dissolution patterns are more uniform. Highlights: Direct pore-network modeling of reactive transport in porous media. Demonstrating the effect of Pe and Da number on dissolution and porosity. Describing the dissolution of porous media and evolution of porosity. Developing a pore-network extracting algorithm. Low PeDa numbers result in uniform concentration and dissolution patterns.